Characterisation of the WAK / WAKL gene family, with a focus on members in Persea americana implicated in defense against Phytophthora cinnamomi - Swart, Velushka (University of Pretoria, 2025)
Dissertation (MSc (Genetics))--University of Pretoria, 2024.